2020
DOI: 10.1007/s40801-020-00201-y
|View full text |Cite
|
Sign up to set email alerts
|

Early Directed Oritavancin Therapy in the Emergency Department May Lead to Hospital Avoidance Compared to Standard Treatment for Acute Bacterial Skin and Skin Structure Infections: A Real-World Retrospective Analysis

Abstract: Objectives Acute bacterial skin and soft tissue infections (ABSSSIs) are a leading cause of presentation to the emergency department (ED). This study aimed to determine the potential impact of utilizing oritavancin in the ED or observation unit (OBS) on hospital inpatient admission. Methods A single-center community teaching hospital developed a pharmacy-led pilot to evaluate the use of oritavancin as a measure to avoid hospital admissions/readmissions in appropriate patients with ABSSSIs. Prior to initiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…Many patients with ABSSSIs, including those with minimal comorbidity and mild or no systemic signs of infection, are hospitalized for several days solely to receive multi-dose and multi-day parenteral antibacterial therapy, which poses a significant financial burden on healthcare systems [5][6][7]. Based on any comorbidities and infection severity, hospitalized patients receiving multi-dose and multi-day parenteral antibacterial therapy may transition to outpatient parenteral or oral antibacterial therapy (OPAT) [7,8].…”
Section: What Are the Antibacterial Effects Of Oritavancin?mentioning
confidence: 99%
See 1 more Smart Citation
“…Many patients with ABSSSIs, including those with minimal comorbidity and mild or no systemic signs of infection, are hospitalized for several days solely to receive multi-dose and multi-day parenteral antibacterial therapy, which poses a significant financial burden on healthcare systems [5][6][7]. Based on any comorbidities and infection severity, hospitalized patients receiving multi-dose and multi-day parenteral antibacterial therapy may transition to outpatient parenteral or oral antibacterial therapy (OPAT) [7,8].…”
Section: What Are the Antibacterial Effects Of Oritavancin?mentioning
confidence: 99%
“…To improve patient clinical outcomes and resource utilization, several centres in the USA have implemented oritavancin as part of a multidisciplinary treatment program for ABSSSIs [12]. Indeed, real-world studies have suggested potential clinical and economic benefits associated with the single-dose IV oritavancin regimen in patients with ABSS-SIs where the treatment reduced disease progression rates [6], infection sequelae from ABSSSI treatment failures [35], 30-day hospital readmission rates [6,35,36] and/or length of hospital stays without affecting readmission rates [5,6]. Furthermore, pharmacoeconomic analyses (from the hospital perspective) of oritavancin versus vancomycin in patients with confirmed or suspected gram-positive ABSSSIs and risk of MRSA in the USA indicate that oritavancin is associated with substantial healthcare cost savings by lowering drug administration burden and reducing hospital admissions [37,38].…”
Section: What Is the Current Clinical Position Of The New IV Formulat...mentioning
confidence: 99%
“…In addition, because oritavancin is administered as a single dose for ABSSSI treatment, it is associated with reduced hospital admission rates and length of stay [ 32–34 ]. In particular, positive benefits were noted in cohorts that received oritavancin compared with cohorts that received vancomycin [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because oritavancin is administered as a single dose for the treatment of ABSSSI, it was found that hospital admission rates and length of stay were reduced in patients receiving oritavancin [ 32–34 ]. Positive benefits were noted particularly in cohorts that received oritavancin versus cohorts that received vancomycin [ 35 , 36 ]. Kimyrsa may facilitate discharge from overwhelmed emergency rooms where bed turnover times are essential for care.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies (Estrada et al [15], Whittaker et al [16], Helton et al [17], and Brownell et al [18]) report observations from real-world clinical settings in terms of either avoidance of hospitalization or early discharge from an inpatient setting by use of single-dose oritavancin for treatment of ABSSSI. Oritavancin was administered in outpatient parenteral antimicrobial therapy programs, emergency departments (EDs), or last day hospital stays in a total of 451 patients with ABSSSI.…”
mentioning
confidence: 99%